A first evaluation of the institutional framework for European monetary policy - Bernhard Duijm (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2000)
The creation of the European Monetary Union (EMU) was a unique event in history: eleven countries gave up essential competences in the field of monetary policy in order to introduce a single common currency, called Euro. While the European Central Bank (ECB) was established, the illtional central banks did not disappear. On the contrary, all central banks of EMU had to be granted institutional ildependence. Together with the ECB, the national central banks (NCBs) of all EU member states constitute the European System of Central Banks (ESCB). The NCBs of the EO countries that have adopted the Euro and the ECB constitute the so-called Eurosystem. The governors of the NCBs of the Eurozone and the members of the Executive Board of the ECB define the monetary policy in EMu. The policy is implemented by the latter and by the NCBs. So, the conduct of the European monetary policy is highly complex. According to the Treaty on EC, the primary objective of the ESCB is to maintain price stability. But generally, even independent central banks do not conduct monetary policy without taking other economic objectives like high employment into consideration. The outcome of monetary policy depends to a great extent on fiscal policies pursued in a country. In countries like the USA or Japan, the central bank has to communicate with one fiscal authority that is responsible for a large share of public expenditures and tax receipts. In EMU, the budget of the European Community is negligible; about 98 per cent of governments' expenditures are spent by national or even subnational bodies (OECD, 2000, 73). So, in Euroland, the European monetary authorities must deal with at least eleven independent fiscal authorities. How can the fiscal interests of the EMU member states be channelled?
urn:nbn:de:bsz:21-opus-19593
Keywords: 330; Europäische Wirtschafts- und Währungsunion; Institutionelle Infrastruktur; Policy-Mix; EU-Staaten